Benign and non-neoplastic tumours of the duodenum - Latos, Wojciech; Kawczyk-Krupka, Aleksandra; Strzelczyk, Natalia; Sieroń, Aleksander; Cieślar, Grzegorz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2019)
This review study describes the problem of duodenal tumours, which are rare but important in gastrological practice. The most common location of small intestinal tumours is the duodenum, and this observation is probably partly due to the greater diagnostic availability for most proximal segments of the small intestine. Among tumours the following should be mentioned – benign: adenomas, lipomas, haemangiomas, and leiomyomas; and malignant: malignant tumours of epithelial origin, primary gastrointestinal stromal tumours, neuroendocrine tumours and carcinoids, lymphomas, sarcomas, teratomas, and secondary metastases. Early duodenal tumour recognition, especially with histological assessment, plays a crucial diagnostic role with future therapeutic implications. In recent years the prevalence of benign duodenal tumours has been rising due to a higher level of clinicians’ doubts and the convenience of gastrointestinal endoscopy; hence, knowledge of this problem is important in routine clinical practice. The method of duodenal tumour treatment should be selected on an individual basis.